MANEJO DA APLICAÇÃO DE AZOSPIRILLUM BRASILENSE E NICOTINAMIDA EM MILHO - RODRIGUES, José Augusto dos Santos; NOGUEIRA, Lavínia Rodrigues; VENDRUSCOLO, Eduardo Pradi; MARTINS, Murilo Battistuzzi; SERON, Cássio de Castro; BORTOLHEIRO, Fernanda Pacheco de Almeida Prado (ANAIS DO ENIC, 2025)
-